2022
DOI: 10.1002/asi.24634
|View full text |Cite
|
Sign up to set email alerts
|

SEntFiN 1.0: Entity‐aware sentiment analysis for financial news

Abstract: Fine-grained financial sentiment analysis on news headlines is a challenging task requiring human-annotated datasets to achieve high performance. Limited studies have tried to address the sentiment extraction task in a setting where multiple entities are present in a news headline. In an effort to further research in this area, we make publicly available SEntFiN 1.0, a humanannotated dataset of 10,753 news headlines with entity-sentiment annotations, of which 2,847 headlines contain multiple entities, often wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Comparatively, Zhao et al ( 2020 ) proposed a RoBERTa as a pre-trained model, which exploits different fine-tuning methods for sentiment analysis and critical entity detection in online financial texts. SEntFiN 1.0 is the most recent publicly available example of a human-annotated dataset of news headlines containing multiple entities (Sinha et al, 2022 ). The authors concluded that deep bidirectional pre-trained language models such as domain-specific BERT fine-tuned to SEntFiN outperform state-of-the-art learning schemes significantly.…”
Section: Artificial Intelligence Approaches For Signal Generationmentioning
confidence: 99%
“…Comparatively, Zhao et al ( 2020 ) proposed a RoBERTa as a pre-trained model, which exploits different fine-tuning methods for sentiment analysis and critical entity detection in online financial texts. SEntFiN 1.0 is the most recent publicly available example of a human-annotated dataset of news headlines containing multiple entities (Sinha et al, 2022 ). The authors concluded that deep bidirectional pre-trained language models such as domain-specific BERT fine-tuned to SEntFiN outperform state-of-the-art learning schemes significantly.…”
Section: Artificial Intelligence Approaches For Signal Generationmentioning
confidence: 99%
“…1) SentFiN 1.0: Entity-aware sentiment analysis for financial news: [33] This human-annotated dataset contains 10,753 news headlines with entity-sentiment annotations, of which 2,847 headlines contain multiple entities, often with conflicting sentiments. For our work purpose, we have dropped the conflicting sentiments.…”
Section: A Phase-1: Existing Datasets For Sentiment Analysismentioning
confidence: 99%
“…For instance, healthcare datasets could facilitate sentiment analysis of patient feedback, improving healthcare service quality. ABSA can help identify investor sentiment towards dif-ferent aspects of a company or its financial performance, potentially predicting stock market trends (Sinha et al, 2022;de França Costa and da Silva, 2018;Ong et al, 2023;Hridoy et al, 2021). Education datasets could uncover student sentiments towards specific aspects of the learning environment, leading to targeted improvements (Alassaf and Qamar, 2020).…”
Section: Is Absa Only For Reviews?mentioning
confidence: 99%